Avaliação do cuidado farmacêutico para hipertensos e/ou diabéticos em unidade de atenção primária à saúde do Ceará: indicadores de processo e de resultados clínico-humanísticos - Firmino, Paulo Yuri Milen (2017)
Studies have shown that, through Pharmaceutical Care, there was improvement in adherence to treatment, quality of life and achievement of therapeutic goals in chronic diseases, such as Systemic Arterial Hypertension and Diabetes Mellitus. Then, the evaluation of a Pharmaceutical Care Unit (UCF) of a Unit of Primary Health Care of Fortaleza was carried out through indicators of process and clinical-humanistic results, in order to assess the benefits of implementing such a service. Data were collected from the pharmacotherapy follow-up records (AFT) of the UCF. Two groups were formed according to the AFT time: 6 months or more (complete AFT) and less than 6 months (Control). In addition, a new data collection was done with AFT patients at least 6 months ago to evaluate maintenance of the benefits. A total of 109 patients were considered: 109 for complete AFT and 115 for AFT (all with p <0.05): systolic blood pressure - the mean was 139.17 mmHg (± 20.6) for 130.77 mmHg (± 16.03); Diastolic blood pressure - the mean of 81.59 (± 11.44) mmHg and became 79.05 (± 9.21) mmHg; Glycemia - went from 145.72 (± 75.8) mg / dL to 120.56 (± 47.56) mg / dL; Cardiovascular risk - an average of 20.05% (± 9.42) which dropped to 18.47% (± 9.06); Treatment adherence - the mean score was 36.81 (± 3.67), increasing to 38.82 (± 3.16) points; Quality of life for hypertension - the mean at baseline was 13.05 (± 9.71) points to 10.98 (± 9.56) points; Quality of life for diabetes - the mean initial score was 17.56 (± 13.51), dropping to an average of 12.48 (± 11.12) points. In the post-AFT analysis, it was observed that the benefits achieved tended to be maintained. Comparative analysis with the Control shows that patients with complete AFT tend to have more expressive results. The UCF was able to identify more than 3 problems / patient, presenting interventions to resolve them with more than 90% acceptance and resolution of more than 80% of these occurrences. The AFT start interview lasts around 40 minutes and the return interview lasts about 20 minutes. The AFT lasts around 10 months and comprises 5 meetings in total with the UCF team. Considering the results analyzed, it can be inferred that the process of Pharmaceutical Care provided at the study site brought clinical and humanistic benefits to the patients.